Technical application of safety and cleaner production technology by underground coal gasification in China. (20th March 2020) - Xie, Jun; Xin, Lin; Hu, Xiangming; Cheng, Weimin; Liu, Weitao; Wang, Zhigang
Abstract: A new residual coal gasification mining system is proposed to utilize in-situ residual coal, mine water, and carbon dioxide for clean combustible gas production. Based on the underground coal gasification (UCG) basic principle, the in-situ coal seam can be transformed into CO, H2, and CH4 by chemical conversion, and can be used for power generation. In the field trials, in-situ georeactors in coal seam were built according to the initial conditions by the shaft method. Based on test results, it's indicated that the hollow-bottom layout makes the in-situ georeactor have good thermal storage performance, which are useful for the generation of combustible gas. Different kinds of gasification agent, such as air, oxygen, steam, carbon dioxide and their mixture were used for syngas production with gas calorific value varying from 3.92 MJ⋅Nm −3 to 10.68 MJ⋅Nm −3 . Adding steam and increasing oxygen concentration can significantly increase syngas concentration and calorific value; two-stage method was used to produce H2 -rich gas and CO2 was used to produce CO-rich gas, which was a useful attempt for CO2 emission reduction and utilization. The syngas was used for power generation after purification, and it can be seen as a cleaner utilization technology of residual coal. The production system provides a feasible way to remining residue coal and clean utilization, and provides technical references for the similar conditions by shaft method. Graphical abstract: The cleaner production systems of underground coal to gas contain gasification agent production system, injecting control system, underground gas production system, gas and water purification system and gas to power generation system. In the field tests, gas production with different gasification agent and ratios were tested, and gas calorific value varied from 3.92 MJ/Nm 3 to 10.68 MJ/Nm 3 . Adding steam and increasing oxygen concentration can significantly increase gas composition and calorific value; two-stage method was used to produce H2 -rich gas and CO2 was used to produce CO-rich gas, which was a useful attempt for CO2 emission reduction and utilization. The two typical shaft method UCG field trials provide a feasible way to remining the residue coal, and provide technical references for the similar conditions by shaft method. Image 1 Highlights: Hollow-bottom georeactors were constructed according to coal seamconditions. Two-stage test of air-steam can obtain up to 44.78% high H2 water gas. CO2 can be used to produce high CO gas, which could reduce carbon emission.